Negara, Ulama, dan Umat dalam Kontestasi Otoritas: Genealogi dan Legitimasi Penentuan Hari Raya Islam Kontemporer: The State, Ulama, or Ummah? : The Genealogy of Authority and The Problem of Legitimacy in Determining Religious Holidays in Contemporary Islam - Hasan Syukur; M. Zainuddin; Al Lastu Nurul Fatim; Ilham Fachmuroji (Jurnal Bimas Islam, 2026)
In Indonesia, the determination of Islamic holidays remains a controversial issue that goes beyond methodological debates between hisab and rukyat. This study aims to analyze: (1) the genealogy of authority regarding the determination of holidays in Islamic tradition; (2) the legitimacy of key actors—the state, religious scholars, and Muslim communities—in contemporary Islam; and (3) the structural factors driving the fragmentation of authority. This study employs a qualitative approach, utilizing a critical literature design for the review and analysis of critical documents through a sociological-phenomenological approach. The analysis employs Max Weber’s typology and Michel Foucault’s genealogy to trace the historical production of religious authority and map the positions of each actor. The results of this study indicate that religious authority for determining holidays is historically constructed, never monolithic, and always contested. While Muslim communities increasingly demonstrate religious autonomy, the state claims rational-legal legitimacy through isbat hearings, and religious scholars and organizations maintain epistemic-traditional legitimacy. The fragmentation of authority is a feature of modern Islam, which demands adaptive dialogue rather than unification. This study employs only a qualitative methodology based on document review and analysis. Furthermore, the findings cannot be generalized as they are limited to the Indonesian context. Consequently, additional research is needed to expand the data and broaden the scope of the analysis.